A long-lived neutron star merger remnant in GW170817: constraints and clues from X-ray observations. Issue 2 (15th November 2018) - Piro, L; Troja, E; Zhang, B; Ryan, G; van Eerten, H; Ricci, R; Wieringa, M H; Tiengo, A; Butler, N R; Cenko, S B; Fox, O D; Khandrika, H G; et al.
Abstract: Multimessenger observations of GW170817 have not conclusively established whether the merger remnant is a black hole (BH) or a neutron star (NS). We show that a long-lived magnetized NS with a poloidal field B ≈ 10 12  G is fully consistent with the electromagnetic dataset, when spin-down losses are dominated by gravitational wave (GW) emission. The required ellipticity ε ≳ 10 −5 can result from a toroidal magnetic field component much stronger than the poloidal component, a configuration expected from an NS newly formed from a merger. Abrupt magnetic dissipation of the toroidal component can lead to the appearance of X-ray flares, analogous to the one observed in gamma-ray burst (GRB) afterglows. In the X-ray afterglow of GW170817, we identify a low-significance (≳3σ) temporal feature at 155 d, consistent with a sudden reactivation of the central NS. Energy injection from the NS spin-down into the relativistic shock is negligible, and the underlying continuum is fully accounted for by a structured jet seen off-axis. Whereas radio and optical observations probe the interaction of this jet with the surrounding medium, observations at X-ray wavelengths, performed with adequate sampling, open a privileged window on to the merger remnant.